Managing and Leading African Universities - Achanga, Pius (International Higher Education, 2012)
The notion of university management and leadership' is currently taking a centre stage within most African states. This is because Africa is witnessing unprecedented rise in the number of university establishments. This article aims to expose the salient issues involving management and leadership of universities in the African context.